Toxocara canis Differentially Affects Hepatic MicroRNA Expression in Beagle Dogs at Different Stages of Infection - Zou, Yang; Zheng, Wen-Bin; He, Jun-Jun; Elsheikha, Hany M.; Zhu, Xing-Quan; Lu, Yi-Xin (Frontiers in Veterinary Science, 2020)
Toxocara canis is a neglected zoonotic parasite, which threatens the health of dogs and humans worldwide. The molecular mechanisms that underlie the progression of T. canis infection remain mostly unknown. MicroRNAs (miRNAs) are small noncoding RNAs that have been identified in T. canis; however, the regulation and role of miRNAs in the host during infection remains incompletely understood. In this study, we determined hepatic microRNAs (miRNAs) expression at different stages of T. canis infection in beagle dogs. Individual dogs were infected by 300 embryonated T. canis eggs and their livers were collected at 12 hpi (hours post-infection), 24 hpi, and 36 dpi (days post-infection). The expression profiles of liver miRNAs were determined using RNA-sequencing. Compared to the control groups, 9, 16, and 34 differentially expressed miRNAs (DEmiRNAs) were detected in the livers of infected dogs at the three infection stages, respectively. Among those DEmiRNAs, the novel-294 and cfa-miR-885 were predicated to regulate inflammation-related genes at the initial stage of infection (12 hpi). The cfa-miR-1839 was predicated to regulate the target gene TRIM71, which may influence the development of T. canis larvae at 24 hpi. Moreover, cfa-miR-370 and cfa-miR-133c were associated with immune response at the final stage of infection (36 dpi). Some immunity related Gene Ontology terms were enriched particularly at 24 hpi. Likewise, Kyoto Encyclopedia of Genes and Genomes pathway analysis showed that many significantly enriched pathways were involved in inflammation and immune responses. The expression level of eight DEmiRNAs was validated using qRT-PCR. These results show that miRNAs play critical roles in the pathogenesis of T. canis during hepatic phase of the parasite development. Our data provide fundamental information for further investigation of the roles of miRNAs in the innate/adaptive immune response of dogs infected by T. canis.